Simultaneous velocity measurement of phases in a liquid-gas system - Musoski Radosław; Stelmach Jacek (Chemical and Process Engineering)
Results of velocity measurements of liquid and gas bubbles in a tank with a self-aspirating disk impeller are analysed. Studies were carried out using a fluorescent dye tracer in the measuring system with two cameras (simultaneous phase velocity measurement) and with one camera (sequential measurement of phase velocity). Based on a comparative analysis of the acquired data it was found that when differences in the phase velocities were small the simultaneous velocity measurement gave good results. However, sequential measurement gives greater possibilities for setting the measuring system and if the analysis of instantaneous velocities is not necessary, it seems to be a better solution.